2013
DOI: 10.1371/journal.pone.0058000
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGF-β Signaling Enables Human Corneal Endothelial Cell Expansion In Vitro for Use in Regenerative Medicine

Abstract: Corneal endothelial dysfunctions occurring in patients with Fuchs' endothelial corneal dystrophy, pseudoexfoliation syndrome, corneal endotheliitis, and surgically induced corneal endothelial damage cause blindness due to the loss of endothelial function that maintains corneal transparency. Transplantation of cultivated corneal endothelial cells (CECs) has been researched to repair endothelial dysfunction in animal models, though the in vitro expansion of human CECs (HCECs) is a pivotal practical issue. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
136
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(144 citation statements)
references
References 41 publications
7
136
0
1
Order By: Relevance
“…The Descemet's membrane and endothelium complex was stripped from corneas and treated with 0.2% collagenase type II and 0.05% hyaluronidase (Worthington Biochemical, Lakewood, NJ) for 3 hours at 37°C. After centrifugation, the primary cells were resuspended in culture medium: OptiMEM-I supplemented with 5% fetal bovine serum, 10 µM Y-27632, 0.5 µg/ml R-spondin and 10 µM SB431542 (TGF-β RI Kinase inhibitor VI) (16) with 0.05% trypsin and 5 mM EDTA in phosphate-buffered saline (PBS) for 10 minutes. Second or third passage human CEC were used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Descemet's membrane and endothelium complex was stripped from corneas and treated with 0.2% collagenase type II and 0.05% hyaluronidase (Worthington Biochemical, Lakewood, NJ) for 3 hours at 37°C. After centrifugation, the primary cells were resuspended in culture medium: OptiMEM-I supplemented with 5% fetal bovine serum, 10 µM Y-27632, 0.5 µg/ml R-spondin and 10 µM SB431542 (TGF-β RI Kinase inhibitor VI) (16) with 0.05% trypsin and 5 mM EDTA in phosphate-buffered saline (PBS) for 10 minutes. Second or third passage human CEC were used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…A major hallmark of the mesenchymal transition is down-regulation of the junctional protein E-cadherin and upregulation of cytoskeletal proteins such as fibronectin and vimentin (19)(20)(21). Moreover, there is also increased expression of α1 (COL1A1) and α2 (COL1A2) chains of type I collagen (21,22), and this is also observed in CEC (12, 16,23). It has been reported that overexpression of transcription factors such as members of SNAI family, SNAI1 and SNAI2, and members of ZEB family, ZEB1 and ZEB2, regulate suppression of E-cadherin expression and overexpression of fibronectin, vimentin, and α-smooth muscle actin (αSMA) (24)(25)(26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Descemet membrane and endothelium complex was stripped from corneas and treated with 0.2% collagenase type II and 0.05% hyaluronidase (Worthington Biochemical, Lakewood, NJ) for 3 h at 37°C. After centrifugation, the primary cells were resuspended in culture medium (OptiMEM I supplemented with 5% fetal bovine serum, 10 M Y27632, 0.5 g/ml R-spondin, and 10 M SB431542 (TGF-␤ receptor inhibitor kinase inhibitor VI) (48)) and plated on 24-well tissue culture plates precoated with FNC Coating Mix (Biological Research Faculty and Facility, Inc., Ijamsville, MD) and laminin (Sigma). For subculture, confluent primary cultures were treated with 0.05% trypsin and 5 mM EDTA in PBS for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 After culturing for 14 days, the FECD-derived CECs and the control CECs were immortalized using SV40 and hTERT to produce iFECD and iHCEC cell lines, respectively. The coding sequences of the SV40 large T antigen and hTERT genes were amplified by PCR and were TA-cloned into a commercial lentiviral vector.…”
Section: Immortalization Of Cecsmentioning
confidence: 99%